Growth and adaptability of provinences and family-within-provenance of Pinus tecunumanii in Northern Mozambique - Dias, Cremildo Riba Gouveia; Mbanze, Aires Afonso (Revista de Ciências Agroveterinárias, 2020)
The goal of company’s forest is to maximize revenues, while minimizing risk and uncertainty. One key strategy to achieve this objective is planting fast-growing and high-yield forest stands. Thus, the Company Florestas do Niassa, operating in Niassa Province, established an experiment trial of five provenances and 28 family-within-provenances of P. Tecunumanii Eguiluz & Perry in northern Mozambique. The experiment was established in Randomized Complete Blocks Design with four lines of replications. Total height, the Diameter at Breast Height (DBH) and survival were assessed at two, four, and eight years. Survival was not significantly different at 8 years and it was above 90% for all provenances, including the control. There were significant growth differences between provenance for the rest of parameters evaluated. The proveniences that best performed at eight years, were Villa Santa, San Rafael del Norte and Yucul. Cluster method used to breakdown the provenances between progenies was useful to identified three distinct groups of progenies: The first, consisted to 12 (41.38%) of the best performing progenies, mostly from Villa Santa and Yucul; the second which was intermediate was composed with seven (24.14%) progenies mostly Yucul and Km 33; The latter consisted of 10 (34.4%) of the worse performing progenies, mostly San Jeronimo and Km 33. Most of the top 10 progenies ranked on the basis of predicted additive genetic effect and genetic gain, belonged to the providence Villa Santa, which was in accordance to the previous clusters results. Most of the progenies (45%) at the level of the 20 best classified individuals also belonged to Villa Santa and can be used for future tree breeding programmes in the environment of Niassa. The selection of the best progenies can be done through DBH, since it had a correlation coefficient above 90% with the volume.